Structural and Semantic Features of Russian Derivative Prepositions pod vidom, pod predlogom and Their French Counterparts - Z. V. Sheremetyeva (Научный диалог)
The results of a comparative analysis of Russian derivative prepositions pod vidom , pod predlogom and their French prepositional counterparts sous couvert de , souscouleur de , sousl’apparence de , en guisede , au motifde , sousprétexte de are presented. The relevance of the study is determined by the need to supplement and clarify the existing lexicographical descriptions of auxiliary units, especially in comparative perspective. The novelty of the study lies in the choice of units for comparative analysis and the approach to their description. The material is journalistic and literary texts of two languages chosen from the electronic text database (text corpus and newspapers archives). The paper raises the question of the degree of conformity of studied units to each other. Special attention is paid to the analysis of the syntactic possibilities of each of the examined prepositional units and their semantic features. The author concludes that the French prepositional expression sous couvert de corresponds to the Russian preposition pod vidom to the greatest degree out of all analyzed units according to its syntactic and semantic properties, and units au motif de and sous prétexte de are the analogues of the Russian pod predlogom .